Splenic infarction following torsion of wandering spleen involving pancreatic tail successfully managed in resource limited setting: a case report - Abel Gashaw Wubie; Berhanu Yirga; Martha H. Goedert (Journal of Medical Case Reports)
Abstract Introduction and importance Wandering spleen is a rare condition characterized by the extreme laxity or absence of ligaments that normally secure the organ in its anatomical position in the left upper quadrant. Torsion of a wandering spleen is an uncommon cause of acute abdominal pain and is rarely diagnosed preoperatively. Torsion involving the distal pancreas is even more unusual. Although patient presentations can be atypical, early diagnosis and prompt intervention can lead to successful outcomes. Case presentation A 40-year-old Black female patient of Amhara ethnicity, from Ethiopia, presented with dull, aching abdominal pain and episodes of vomiting. After initial physiological stabilization and radiologic evaluation, laparotomy was performed, revealing torsion of a wandering spleen with involvement of the pancreatic tail, accompanied by adhesions of the small bowel and omentum. Following the release of adhesions, a splenectomy was performed. The patient was discharged in stable condition and continued to do well during follow-up visits. Conclusion Despite its rarity and potential for atypical presentations, a high index of suspicion for torsion of a wandering spleen is essential, particularly in patients with risk factors. With prompt diagnosis and timely intervention, patients with this condition can achieve favorable outcomes.